Prediabetes prevalence and awareness by race, ethnicity, and educational attainment among U.S. adults - Formagini, Taynara; Brooks, Joanna Veazey; Roberts, Andrew; Bullard, Kai McKeever; Zhang, Yan; Saelee, Ryan; O'Brien, Matthew James (Frontiers in Public Health, 2023)
Racial and ethnic minority groups and individuals with limited educational attainment experience a disproportionate burden of diabetes. Prediabetes represents a high-risk state for developing type 2 diabetes, but most adults with prediabetes are unaware of having the condition. Uncovering whether racial and ethnic and educational disparities also occur in the prediabetes stage could help inform strategies to support health equity in preventing type 2 diabetes and its complications. We examined prediabetes and prediabetes awareness prevalence and prevalence ratio according to race and ethnicity and educational attainment. This study conducted a pooled cross-sectional analysis of the National Health and Nutrition Examination Survey data from 2011 to March 2020. The final sample comprised 10,262 adults who self-reported being Asian, Black, Hispanic, or White. Prediabetes was defined using A1c and fasting plasma glucose values. Those with prediabetes were classified as “aware” or “unaware” based on survey responses. We calculated prevalence ratios (PR) to assess the relationship between race and ethnicity and educational attainment with prediabetes and prediabetes awareness controlling for sociodemographic, health and healthcare-related, and clinical characteristics. In the fully adjusted logistic regression models, Asian, Black, and Hispanic adults had a statistically significant higher risk of prediabetes than White adults (PR:1.26 [1.18,1.35], PR:1.17 [1.08,1.25], and PR:1.10 [1.02,1.19], respectively). Adults completing less than high school and high school had a significantly higher risk of prediabetes compared to adults with a college degree (PR:1.14 [1.02,1.26] and PR:1.12 [1.01,1.23], respectively). We also found that Black and Hispanic adults had higher rates of prediabetes awareness in the fully adjusted model than White adults (PR:1.27 [1.07,1.50] and PR:133 [1.02,1.72], respectively). The rates of prediabetes awareness were consistently lower among those with less than a high school education relative to individuals who completed college (fully-adjusted model PR:0.66 [0.47,0.92]). Disparities in prediabetes among racial and ethnic minorities and adults with low educational attainment suggest challenges and opportunities for promoting health equity in high-risk groups in expanding awareness of prediabetes and increasing access to evidence-based interventions to prevent type 2 diabetes.